Getting It Right for Every Child: A National Policy Framework to Promote Children's Well‐being in Scotland, United Kingdom. Issue 2 (June 2016) - COLES, EMMA; CHEYNE, HELEN; RANKIN, JEAN; DANIEL, BRIGID
Abstract : Policy Points : Getting It Right for Every Child (GIRFEC), a landmark policy framework for improving children's well‐being in Scotland, United Kingdom, is a practice initiative signifying a distinct way of thinking, an agenda for change, and the future direction of child welfare policy. GIRFEC represents a unique case study of national transformative change within the contexts of children's well‐being and universal services and is of relevance to other jurisdictions. Implementation is under way, with an understanding of well‐being and the requirement for information sharing enshrined in law. Yet there is scope for interpretation within the legislation and associated guidance. Inherent tensions around intrusion, data gathering, professional roles, and balancing well‐being against child protection threaten the effectiveness of the policy if not resolved. Context: Despite persistent health inequalities and intergenerational deprivation, the Scottish government aspires for Scotland to be the best country for children to grow up in. Getting It Right for Every Child (GIRFEC) is a landmark children's policy framework to improve children's well‐being via early intervention, universal service provision, and multiagency coordination across organizational boundaries. Placing the child and family "at the center, " this approach marks a shift from welfare to well‐being, yet there is still a general lack of consensus over how well‐being is defined and measured. As an umbrella policy framework with broad reach, GIRFEC represents the current and future direction of children's/family policy in Scotland, yet large‐scale practice change is required for successful implementation. Methods: This article explores the origins and emergence of GIRFEC and presents a critical analysis of its incremental design, development, and implementation. Findings: There is considerable scope for interpretation within the GIRFEC legislation and guidance, most notably around assessment of well‐being and the role and remit of those charged with implementation. Tensions have arisen around issues such as professional roles; intrusion, data sharing, and confidentiality; and the balance between supporting well‐being and protecting children. Despite the policy's intentions for integration, the service landscape for children and families still remains relatively fragmented. Conclusions: Although the policy has groundbreaking potential, inherent tensions must be resolved and the processes of change carefully managed in order for GIRFEC to be effective. It remains to be seen whether GIRFEC can fulfil the Scottish government's aspirations to reduce inequalities and improve lifelong outcomes for Scotland's children and young people. In terms of both a national children's well‐being framework within a universal public service context and a distinct style of policymaking and implementation, the Scottish experience represents a unique case study of whole‐country, transformational change and is of relevance to other jurisdictions.